Dynamic evolution of postoperative hemodynamics in moyamoya angiopathy: a quantitative assessment of 4D Flow MRI and prognostic relevance - Xia, Chao; Fu, Mingzhu; Tian, Rui; Ren, Yutao; Xu, Xu; Zhang, Jinge; Xia, Chunchao; You, Chao; Hu, Na; Lui, Su; Li, Rui; Liu, Yi (Frontiers in Neurology, 2025)
PurposeThe hemodynamic mechanisms underlying revascularization efficacy in moyamoya angiopathy (MMA) and their prognostic implications remain incompletely characterized. This study leverages four-dimensional flow magnetic resonance imaging (4D Flow MRI) to investigate longitudinal hemodynamic changes at the carotid siphons of MMA patients undergoing revascularization, and to evaluate their association with surgical outcomes.MethodsA prospective cohort of 35 consecutive MMA patients undergoing unilateral revascularization was enrolled at West China Hospital from July 2018 to January 2020. Using 4D Flow MRI, hemodynamic parameters, including mean/maximum flow, velocity, and wall shear stress, were quantified in the ipsilateral and contralateral carotid siphons at three timepoints: baseline, 1-week postoperative, and 1-year follow-up. Repeated-measures analysis of variance with Bonferroni correction was employed to compare longitudinal changes and correlate findings with 1-year clinical (excellent, good, and poor) and imaging (cerebral perfusion status and Matsushima collateralization grade) outcomes.ResultsBaseline and 1-week postoperative assessments revealed that only velocity within contralateral carotid siphon significantly increased (mean velocity: from 20.52 [15.34–28.78] cm/s to 23.70 [16.01–39.06] cm/s, p = 0.026; maximum velocity: from 29.26 [19.68–38.39] cm/s to 33.22 [20.99–50.95] cm/s, p = 0.001). However, both carotid siphons demonstrated significant reductions in mean and maximum flow (ipsilateral: mean flow from 1.92 [0.65–3.53] mL/s to 1.31 [0.58–2.87] mL/s, p = 0.043, maximum flow from 2.61 [0.93–4.95] mL/s to 1.97 [0.89–3.90] mL/s, p = 0.036; contralateral: mean flow from 2.87 [0.91–4.12] mL/s to 2.14 [0.81–3.78] mL/s, p = 0.010) at 1-year follow-up. Lower contralateral siphon flow at follow-up correlated with “good” (but not “excellent”) clinical outcomes. Reduced flow in both siphons was associated with improved cerebral perfusion and robust collateralization (Matsushima grades A/B), whereas no changes were observed in patients with poor collaterals (Matsushima grade C).Conclusion4D Flow MRI reveals delayed, bilateral hemodynamic remodeling in MMA at 1-year post-revascularization. These changes correlate with clinical improvement, enhanced perfusion, and collateral development, underscoring the technique utility in monitoring long-term cerebrovascular adaptation.